From Melancholia to Depression Disordered Mood in Nineteenth-Century Psychiatry - Jansson, Åsa (Mental Health in Historical Perspective, 2021)
This open access book maps a crucial but neglected chapter in the history of psychiatry: how was melancholia transformed in the nineteenth century from traditional melancholy madness into a modern biomedical mood disorder, paving the way for the emergence of clinical depression as a psychiatric illness in the twentieth century? At a time when the prevalence of mood disorders and antidepressant consumption are at an all-time high, the need for a comprehensive historical understanding of how modern depressive illness came into being has never been more urgent. This book addresses a significant gap in existing scholarly literature on melancholia, depression, and mood disorders by offering a contextualised and critical perspective on the history of melancholia in the first decades of psychiatry, from the 1830s until the turn of the twentieth century.